2018
DOI: 10.1177/0261927x18810730
|View full text |Cite
|
Sign up to set email alerts
|

Re-evaluating the Prestige of Regional Accents in Netherlandic Standard Dutch: The Role of Accent Strength and Speaker Gender

Abstract: This article investigates three neglected determinants of native speakers' attitudes toward regional accent variation in Netherlandic Standard Dutch, namely, accent strength, speaker gender, and the evaluation dimension dynamism. Nineteen participants first rated 126 speech clips representing three regional accents (Randstad, Groningen, Limburg) in terms of the expected regional origin of the speakers and their accent strength. In a subsequent speaker evaluation study, 148 participants rated the 16 clips that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Previous research over several decades and in many parts of the world has revealed a consensus that LAs are bidimensional and usually operate between status and solidarity (El-Dash and Busnardo, 2001;Genesee and Holobow, 1989). Recently, the dynamism dimension has been revealed as a separate dimension to be added to status and solidarity (Grondelaers et al, 2019;Kristiansen, 2001Kristiansen, , 2009Zahn and Hopper, 1985). The current research revealed a three-dimensional model with dynamism as the predominant dimension instead of status.…”
Section: Discussionmentioning
confidence: 61%
“…Previous research over several decades and in many parts of the world has revealed a consensus that LAs are bidimensional and usually operate between status and solidarity (El-Dash and Busnardo, 2001;Genesee and Holobow, 1989). Recently, the dynamism dimension has been revealed as a separate dimension to be added to status and solidarity (Grondelaers et al, 2019;Kristiansen, 2001Kristiansen, , 2009Zahn and Hopper, 1985). The current research revealed a three-dimensional model with dynamism as the predominant dimension instead of status.…”
Section: Discussionmentioning
confidence: 61%
“…We cannot state too emphatically, to begin with, that the statistics used in this paper represent exploratory techniques which help us group and classify data, but which do not reveal anything about the statistical significance of the differences we observe. Another limitation of our findings is the fact that evaluations were extracted in response to variety labels, which do not always work well (we have suggested in this respect that the label 'ThuisFamilie' is not a perfect fit for the variety it denotes), and which inevitably abstract away from pivotal impression determinants such as accent strength (Grondelaers, Van Hout & Van Gent, 2019): the fact that the status of even the least prestigious accent increases as it gets milder, is impossible to accommodate in this sort of task. What the present experiment has shown is that it is possible to get a firm experimental grip on the perceptual and ideological correlates of standard language dynamics of Belgian Dutch, and that researchers who plan speaker evaluation experiments to investigate these dynamics had better conduct an EFR-experiment as a leg-up.…”
Section: Resultsmentioning
confidence: 98%
“…They were recorded in a soundproof recording studio. We restrict ourselves to men so as to avoid any potential confounding effects of gender stereotypes (e.g., Trudgill 1974;Grondelaers, Van Hout & Van Gent 2018) or differences in how listeners evaluate women versus men as dialect speakers (Fabricius 2006), and we record young men so as to mimic the expected age of entry-level law firm candidates.…”
Section: Methodsmentioning
confidence: 99%